Community Structure of Gastropoda in The Intertidal Zone of Waloindi Beach, Wakatobi - Aba, La; I.A, Dyah Pramesthi; Awiani, Wa; Yanti, Yanti (Jurnal Biologi Tropis, 2025)
Gastropods commonly known as snails, are the largest class of the mollusc phylum. The body of gastropods is equipped with tentacles, eyes, and radula, as well as a well-developed head, where the body of this animal is generally wrapped in a shell. Gastropods have a very wide distribution, both in fresh water, sea, mangrove ecosystems and on land. This study aims to determine the structure of the gastropod community in the intertidal zone of Waloindi Beach, Wakatobi. Research data were obtained through exploration methods at three observation stations, each measuring 100 x 20 meters. Community structure data in the form of density, diversity index, evenness index and dominance index were analyzed descriptively quantitatively. The results of the study found 16 types of gastropods classified into 6 orders, namely Littorinimorpha (genera Conomurex, Stombus, Lambis, and Lentigo). Neogastropoda Order (genus Vasum, Conus, Mitra and Cymbiola) and Trochida Order (genus Turbo and Trochus), as well as Vetigastropoda, Cycloneritida, and Caenogastropoda orders (each found one genus, namely Angaria, Neritida and Cerithium). The highest density of gastropod species was found at station II (seagrass sand substrate) of 0.0635 (ind/m2), while the lowest density of species was found at station I (sand substrate) of 0.0245 (ind/m2). Strombus mutabilis is the species with the highest density, namely 0.023 (ind/m2), and Mitra mitra is the species with the lowest density, namely 0 (ind/m2). The highest gastropod diversity index was found at station II, namely 2.3209 and the lowest diversity was found at station I, namely 2.0643. Overall, the Shannon-Wiener diversity level (H’) of gastropods at the research location was 2.443839, included in the moderate category. The highest gastropod evenness index (E) was found at station II, which was 0.837088931 and the lowest at station I, which was 0.744545361. Overall, the evenness index at the research location was classified as high (E> 0.6). The highest gastropod dominance index (C) was found at station II, which was 0.191005917 and the lowest at station III, which was 0.127595156. Based on these criteria, the dominance index of gastropod species at the research location was classified as low.